Tampa Garam: Konsep Pendidikan Kristen Kontekstual di Maluku - Dembris Kristian Soeki (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2021)
Abstract. This article offers a medium for Christian Education that was born from the traditions and customs that exist in the life of Christian families in Maluku. The Christian Education Media is the tradition tampa garam, which is a tradition of conversation at the food table in the culture of the Maluku people. This tradition has been adopted by Christian families in Maluku as a medium for conveying Christian values to children. Through a qualitative approach and literature study, it could be concluded that the tampa garam tradition contains values that are in harmony with Christian teachings such as love, peace, harmony, and reconciliation.Abstrak. Artikel ini menawarkan salah satu media Pendidikan Kristen yang lahir dari tradisi-tradisi dan kebiasaan-kebiasaan yang ada dalam kehidupan keluarga Kristen di Maluku. Media Pendidikan Kristen yang dimaksud adalah tradisi tampa garam, yang merupakan tradisi percakapan di meja makan dalam kebudayaan masyarakat Maluku. Tradisi ini telah diadopsi oleh keluarga-keluarga Kristen di Maluku sebagai media penyampaian nilai-nilai Kekristenan kepada anak-anak. Melalui pendekatan kualitatif dan studi kepustakaan dapat disimpulkan bahwa tradisi tampa garam mengandung nilai-nilai yang selaras dengan ajaran-ajaran Kristiani seperti kasih, kedamaian, keharmonisan, dan rekonsiliasi.